Intra-specific variations in Schistosoma mansoni and their possible contribution to inconsistent virulence and diverse clinical outcomes - Dannenhaus, Tim A; Winkelmann, Franziska; Reinholdt, Cindy; Bischofsberger, Miriam; Dvořák, Jan; Grevelding, Christoph G; Löbermann, Micha; Reisinger, Emil C; Sombetzki, Martina (PLoS neglected tropical diseases, 2024)
BACKGROUND: Schistosoma mansoni was introduced from Africa to the Americas during the transatlantic slave trade and remains a major public health problem in parts of South America and the Caribbean. This study presents a comprehensive comparative analysis of three S. mansoni strains with different geographical origins-from Liberia, Belo Horizonte and Puerto Rico. We demonstrated significant variation in virulence and host-parasite interactions. METHODS: We investigated the phenotypic characteristics of the parasite and its eggs, as well as the immunopathologic effects on laboratory mouse organ systems. RESULTS: Our results show significant differences in worm morphology, worm burden, egg size, and pathologic organ changes between these strains. The Puerto Rican strain showed the highest virulence, as evidenced by marked liver and spleen changes and advanced liver fibrosis indicated by increased collagen content. In contrast, the strains from Liberia and Belo Horizonte had a less pathogenic profile with less liver fibrosis. We found further variations in granuloma formation, cytokine expression and T-cell dynamics, indicating different immune responses. CONCLUSION: Our study emphasizes the importance of considering intra-specific variations of S. mansoni for the development of targeted therapies and public health strategies. The different virulence patterns, host immune responses and organ pathologies observed in these strains provide important insights for future research and could inform region-specific interventions for schistosomiasis control.
Keywords: Liver; Liberia; játra; cytokiny; virulence; mužské pohlaví; Mice; Cytokines; Libérie; slezina; Schistosoma mansoni; ženské pohlaví; zvířata; Virulence; Host-Parasite Interactions; Schistosomiasis mansoni; myši; interakce hostitele a parazita; Portoriko; Female; Spleen; schistosomiasis mansoni; Puerto Rico; Male; Animals